Looking at the Golden Ratio from the Blood Pressure Perspective: Assessing the Hypertensive Patients and Normotensive Subjects - Atmaca, Hasan; Cuglan, Bilal; Karagöz, Zuhal Karaca; Yalta, Kenan; Yetkin, Ertan (Current Hypertension Reviews, 2024)
BackgroundThe representatives of mathematical concepts and indices allied to the Golden Ratio (GR) have been shown in the human body in superimposed human hands, phalangeal lengths of the digits, human ears, and the cardiovascular system. Recently, it has been demonstrated that the systolic blood pressure (SBP) to diastolic blood pressure (DBP) ratio measured by ambulatory blood pressure monitoring (ABPM) is close to GR. Accordingly, we aimed to evaluate the ratios between the SBP, DBP, and PP in normotensive and hypertensive patients who were on medical treatment or not, to assess the existence of golden proportions in 24-hour ambulatory blood pressure monitoring results.Material and MethodFive hundred and twenty-nine patients who underwent ABPM were retrospectively enrolled in the study population. The ABPM was programmed to measure blood pressure every 30 min during the daytime and 60 min night time. Based on the ABPM results, patients were classified as hypertensive (SBP/DBP≥130/80 mmHg) and normotensive (SBP/DBP<130/80 mmHg), depending on ESC/ESH 2018 guidelines. They were also divided into two subgroups: medicated and nonmedicated. Systolic to diastolic blood pressure ratio (SBP/DBP) and diastolic blood pressure to pulse pressure (DBP/PP) were calculated in the usual fashion in all study populations and subgroups.ResultsAfter the exclusion of 133 patients who did not fulfill the inclusion criteria, 396 patients were included in the statistical analysis. Mean SBP/DBP ratios were 1.66±0.15 in all the study population, 1.63±0.11 in normotensive without medication, 1.66±0.13 in normotensive with medications, 1.62±0.15 in hypertensive without medication, and 1.76±0.20 with medications.ConclusionWe have documented that SBP to DBP ratios of untreated patients, irrespective of having normal or high blood pressure, run close around the GR. However, SBP to DBP ratios of patients having antihypertensive treatment are far from the GR.Clinical Trial Registration Number01.11.2022.247338
Keywords: hypertension